2019
DOI: 10.1039/c8ra08910h
|View full text |Cite
|
Sign up to set email alerts
|

Study of diffuse phase transition and relaxor ferroelectric behavior of Ba0.97Bi0.02Ti0.9Zr0.05Nb0.04O3 ceramic

Abstract: In the present work, structural property of polycrystalline sample Ba0.97Bi0.02Ti0.9Zr0.05Nb0.04O3 (BBTZN) prepared by a molten-salt method were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 61 publications
2
20
0
Order By: Relevance
“…( T C ≠ T 0 ) shows that the phase transition is of a first order type. 55 The broadened peaks correspond to the diffuse type transition in this composition, a distinctive feature of a disordered perovskite structure.…”
Section: Resultsmentioning
confidence: 86%
“…( T C ≠ T 0 ) shows that the phase transition is of a first order type. 55 The broadened peaks correspond to the diffuse type transition in this composition, a distinctive feature of a disordered perovskite structure.…”
Section: Resultsmentioning
confidence: 86%
“… 39 where c denotes the Curie constant and 1 < γ < 2 is defined as the diffuseness degree indicator of the character of the phase transition. 40 Linear relationships are observed in the plot of as a function of log( T − Tm) at 10 kHz frequency for the compositions x = 0.75 and x = 0.8 as shown in ( Fig. 7a and b ).…”
Section: Resultsmentioning
confidence: 68%
“…where c denotes the Curie constant and 1 < g < 2 is dened as the diffuseness degree indicator of the character of the phase transition. 40 Linear relationships are observed in the plot…”
Section: Dielectric Studymentioning
confidence: 97%
“…Based on the Smolensky-Isupov's theory of DPT, it can be concluded that with the increase in dopant concentration, the competition between occupancy of the same B-site with parent Ti and dopant Nb increases, which causes an increase in composition fluctuation of different polar micro-regions and hence increase in DPT nature. Coexistence of multiions at B-site also tends to cause inhomogeneous distribution and disordered crystal structure [29], which can account diffuse phase transition of the Nb-doped NBT ceramics.…”
Section: Resultsmentioning
confidence: 99%